Effect of Concentration on Isomerization of Rhodanine Derivatives of Merocyanine Dyes in Polar Solvents. (27th August 2014) - Dimitriev, O. P.; Grytsenko, K. P.; Tolmachev, O. I.; Slominskii, Yu. L.; Kudinova, M. A.; Schrader, S.
Abstract : Rhodanine derivatives of merocyanine dyes with residues of 1, 3, 3-trimethyl-3H-indole and 3-ethylbenzothiazoline have been found to possess two molecular forms in diluted solutions of polar solvents such as dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidinone. The first molecular form was observed to prevail at low concentrations of the dyes, normally up to 10 −5  M. The second one prevails at higher concentrations and is displayed through a new band in the electronic absorption spectrum, which is red-shifted with respect to the absorption band of the first form. No similar effect was found for these dyes by use of nonpolar solvents or upon alkyl-substitution of the molecules at nitrogen atom in the rhodanine moiety. We assign the above two forms to different molecular isomers and the analogous spectral changes were shown to take place by light or heat influence which correspond to a typical isomerization effect for the related merocyanine dyes. It is discussed that the isomer transformation is facilitated by the increased mobility of the proton bonded to the nitrogen atom of the rhodanine moiety in the polar environment and the increased amount of dye-dye collisions.